A clinical evaluation of the whitening capability and sensitivity effects of 3M zaris professional tooth whitening system with and without tray reservoirs - David, Mark Kenneth Nery
The purpose of this study was to compare the efficacy of 3M? Zaris? Professional Tooth Whitening System (16% carbamide peroxide) when using bleaching trays with and without tray reservoirs, specifically to compare the whitening capability and incidences of sensitivity and adverse reactions such as soft tissue irritation. The study was an in-vivo experimental, single-blind clinical trial. The authors recruited 27 subjects who fit the inclusion criteria, and with maxillary anterior teeth of shade A3 or darker on the Vita shade guide. The maxillary lateral incisors were the teeth evaluated in the study. Individual trays fabricated in a split mouth design wherein the right side had a gel retention insert as a reservoir, while the left side had none. Given instructions, the subjects used the product for 1-week at night for at least 4 hours. The results indicate a significant decrease in the mean ranking of each group at succeeding recalls with p-value=0.0001. There was no statistical significant difference between whitening results on teeth bleached with and without reservoirs (p value>0.05). Sensitivity results showed that there were no significant differences between recalls. Other findings show that there were incidences of soft tissue irritation: 15.2% on the gingiva, 4.1% on the buccal mucosa, 4.7% on the palate, 7.6% on the tongue, 10.5% on the throat and 4.7% on the lips. The adverse reactions (sensitivity and soft tissue irritation) were mild and transient, and quickly subsided after the active treatment. It can be concluded based on the study that 3M? Zaris? Professional Tooth Whitening System (16% carbamide peroxide) is effective in whitening teeth with and without tray reservoirs. The incidence of tooth sensitivity and soft tissue irritation were minimal, mild and transient, thus 3M? Zaris? Professional Tooth Whitening System can be considered safe, but dentist supervision is advisable.